Brief Report: Patients With Primary Sjögren's Syndrome Who Are Positive for Autoantibodies to Tripartite Motif–Containing Protein 38 Show Greater Disease Severity. Issue 3 (March 2016) - Wolska, Nina; Rybakowska, Paulina; Rasmussen, Astrid; Brown, Michael; Montgomery, Courtney; Klopocki, Arkadiusz; Grundahl, Kiely; Scofield, Robert H.; Radfar, Lida; Stone, Donald U.; Anaya, Juan M.; Ice, John A.; et al.
Abstract : Objective: Autoantibodies reactive with Ro52 (tripartite motif−containing protein 21 [TRIM21]) are detected in 70% of patients with primary Sjögren's syndrome (SS). TRIM21 belongs to a 34‐member C‐IV family of TRIM proteins. Although autoantibodies against other TRIM proteins within the C‐IV family have been detected in the sera of patients with primary SS, their clinical relevance remains unclear. This study was undertaken to investigate the frequency of anti‐TRIM38 in patients with primary SS and evaluate its association with various clinical measures of the disease. Methods: Serum samples from patients with primary SS (n = 235) and controls (n = 50) were analyzed for reactivity with in vitro−transcribed and −translated 35 S‐methionine−labeled TRIM38 protein. The associations of anti‐TRIM38 with various laboratory and clinical measures of primary SS were evaluated. Reactivity of anti‐TRIM38 with different structural domains of TRIM38 was analyzed. Affinity‐purified anti‐TRIM38 antibodies were used to immunoprecipitate TRIM21. Results: TRIM38‐reactive autoantibodies were detected in the sera of 24 of the 235 patients with primary SS and 2 of the 50 controls. Anti‐TRIM38 positivity was significantly associated with the presence of anti‐Ro60, anti‐Ro52, anti‐La, rheumatoid factor, and hypergammaglobulinemia. Clinically, anti‐TRIM38 was associated with significantly higher ocular surface staining scores, lower Schirmer's test scores, and minor labial salivary gland biopsy focus scores of ≥3.0. Anti‐TRIM38 antibodies mainly recognized the cortactin‐binding protein 2 (CortBP‐2; amino acids 128–238) and the B30.2/SPRY (amino acids 268–465) domains on TRIM38. Affinity‐purified antibodies to TRIM38–CortBP‐2 and TRIM38–B30.2/SPRY domains reacted with TRIM21. Conclusion: Our data demonstrate that anti‐TRIM38 specificity arising in a subset of patients with primary SS is associated with increased severity of the disease.